2015
DOI: 10.1210/jc.2014-3551
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of ACTH Stimulation Test in Determining the Subtypes of Primary Aldosteronism

Abstract: The ACTH stimulation test under 1 mg DST is useful to determine the subtypes of PA, especially in unilateral and bilateral PA, and may guide further treatment in PA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 36 publications
6
63
1
Order By: Relevance
“…After our report, another group has performed a similar study analyzing the diagnostic capacity of ACTH stimulation test under dexamethasone suppression to diagnose APA, with the result consistent with ours in that the test is useful for detecting unilateral PA 22 . There have also been studies that tested the efficiency of ACTH stimulation test without dexamethasone suppression, but they were not so successful in differentiating the two major subtypes in PA patients 23,24 , suggesting the importance of dexamethasone administration.…”
Section: Differential Regulation Of Blood Aldosterone Level In Apa Ansupporting
confidence: 84%
“…After our report, another group has performed a similar study analyzing the diagnostic capacity of ACTH stimulation test under dexamethasone suppression to diagnose APA, with the result consistent with ours in that the test is useful for detecting unilateral PA 22 . There have also been studies that tested the efficiency of ACTH stimulation test without dexamethasone suppression, but they were not so successful in differentiating the two major subtypes in PA patients 23,24 , suggesting the importance of dexamethasone administration.…”
Section: Differential Regulation Of Blood Aldosterone Level In Apa Ansupporting
confidence: 84%
“…The present data showed that the AST had the highest positive rate among all confirmatory tests in both the unilateral and bilateral groups. Sonoyama et al and Jiang et al reported that the ACTH stimulation test under dexamethasone suppression is highly sensitive for distinguishing APA from IHA or non-PA [12,13]. In this study, the AST-positive rate was not different between the groups using a cut-off value of 8.5 for PAC max /F in AST [9].…”
Section: Discussionmentioning
confidence: 60%
“…However, AVS is far from easy to perform for all patients with PA because of some problems (e.g., high cost, adrenal phlebography-associated complications, and the high level of technical skill and experience needed for successful cannulation of the (right) adrenal vein). Recent reports have shown that the ACTH stimulation test with 1-mg dexamethasone is useful for determining the subtype of PA [12,13]. However, little has been reported about which confirmatory tests are useful in determining the subtype of PA. Our objective was to determine the most useful confirmatory test and the cut-off value to distinguish the subtype of PA.…”
Section: Astmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic accuracy was around 80-90%, so this test might be used to select patients who have high probability of unilateral disease and definitely require AVS [57,58].…”
Section: Clinical Management Of Adrenal Tumors 74mentioning
confidence: 99%